Ownership choice of cross-border acquisitions by developed and emerging economy market firms: The case of Indian services sector - Gwi, Qiao Ning (2016)
In this paper, we expand the understanding of cross-border acquisitions by investigating how institutional distance (high versus low), type of service (soft versus hard) and country-of-origin effect (emerging versus developed) influence the firms’ acquisition behaviour (full versus partial) in services sector in India. Adopting binomial logistic regression model, we tested the hypothesized relationships using a sample of 364 cross-border acquisitions undertaken in Indian services sector over the period 2005-2015. We found that institutional distance, type of service and country-of-origin effects have significant impact on ownership participation in cross-border acquisitions. Specifically, we found that when acquisitions involve hard services and high institutional distance, acquirers from emerging economies are more likely to opt for full acquisition. However, acquirers from developed economies will opt for partial acquisition under the similar circumstances. All these findings are robust to alternative ownership measures. This study enhances the understanding of conditions under which the multinational enterprises (MNEs) will choose full versus partial ownership in acquiring services firms. Specifically, this paper provides insights on how MNEs from emerging and developed economies vary in their ownership behaviour while acquiring services firms in India.